EMENDA CONSTITUCIONAL Nº 95/2016: AMEAÇAS E DESAFIOS AOS INSTITUTOS FEDERAIS (Revista Contexto & Educação, 2021)
This paper seeks at investigate the effects of the freeze on public spending, via Constitutional Amendment No. 95/2016, on the integrated high school of Vocational Education. Based on a theoretical discussion, it was pointed out the advances in Professional Education brought by the Federal Institutes as well as the challenges that face the approval of Constitutional Amendment Nº. 95/2016. Considering the conceptions that give rise to the debate on the construction of an emancipatory Vocational Education, from the perspective of work as an educational principle and with human emancipation as a goal, it is possible to contextualize the moment that Education is going through in the country, serving the project of State and society.